Pergeseran Sentral Geopolitik Internasional, dari Heartland ke Asia Pasifik, Apa Geopolitic Leverage Indonesia ? - Zulkarnain Zulkarnain; Hendra Maujana Saragih; Safrizal Rambe; Hendrajit - Hendrajit (Universitas Nasional, 2018)
Indonesia has strategic geopolitics in global interaction, besides its position between two oceans and two continents which is an opportunity for how big a role that can be played on the international stage, also has a variety of natural resources. But this nation is not able to